La Saint-Barthélemy dans la tourmente de l’affaire Dreyfus - Frank Lestringant (Etudes Epistémè)
This article looks at the periodical nature of Saint Bartholomew's Day, the ripples of which spread from century to century, to consider one of its most famous returns, which occurred at the end of the 19th century, at the time of the Dreyfus Affair. It wasn’t a real Saint Bartholomew's Day, but its fantasy, a demented dream or insistent nightmare, present in the mouths of anti-Dreyfus supporters as well as early Dreyfus supporters. This rebound in the Dreyfus affair erupted in January 1898 with Émile Zola's "J'accuse...", sparking an outpouring of hatred in the opposing camp. It has been said that the Dreyfus affair was the baptism of intellectuals as public figures in France. Belonging to a religious minority was a catalyst for awareness. This was obvious for intellectuals of Jewish origin, but also for Protestants, an intellectual minority that was all-powerful in the early days of the Republic. Nationalists and antidreyfusards alike stigmatised the two religious minorities, blaming them for all of France's misfortunes.